The Effect of Problem Based Learning Based Sosio-Scientific Issues on Scientific Literacy and Problem-Solving Skills of Junior High School Students - Hestiana Hestiana; Dadan Rosana (Universitas Negeri Yogyakarta, 2020)
This study aims to analyze the effect of the Sosio-Scientific Issues (SSI) based Problem Based Learning (PBL) on increasing scientific literacy and problem-solving skills of junior high school students. The type of research is Quasi experiment with Nonequivalent Control Group Design. The population included class VII Junior High School of 6 Yogyakarta that consisting of seven classes in the 2019/2020 school year. The sample is determined by the Purposive Sampling technique. The research instruments were pretest and posttest questions of scientific literacy and students' problem-solving skills. Hypothesis testing is done with MANOVA and effect size calculation to find out how much influence is given. Based on the MANOVA test, the Sig value is 0,000 that less than α (0.05) so that Ha is accepted (H0 is rejected). As for the calculation of the effect size obtained a score of 0.897 (high enough), which means that SSI-based PBL has a significant effect on increasing scientific literacy and a score of 1,027 (high), which means that SSI-based PBL has a high effect on improving students' problem-solving skills. Based on these results it can be concluded that PBI based on SSI affects the increasing scientific literacy and problem-solving skills.